Bioclimatic chart analysis in three climate zones in Cyprus - Katafygiotou, Martha; Serghides, Despina Kyprianou (My University, 2015)
The concept of bioclimatic design is based on the development of an architectural design adapted to environmental conditions. The utilization of the favourable climatic elements can offer to the users, indoor thermal comfort conditions and at the same time it minimizes the energy consumption which is needed for heating and cooling. This paper provides the bioclimatic analysis for three different climatic zones in Cyprus, coastal, inland and mountainous. The building bioclimatic charts of V. & A. Olgyay are used to examine whether passive strategies can provide indoor thermal comfort in the buildings in these zones. The results of bioclimatic charts are studied in conjunction with the climatic data for the three climatic areas. These are compared and investigated in order to find whether there is sufficient amount of solar radiation for passive heating needed to achieve thermal comfort during winter. The study concludes to a preliminary guide of passive design strategies for buildings, as an outcome of the bioclimatic charts analysis for coastal, inland and mountainous zones in Cyprus. The results can be used for locations with similar climatic conditions.
Keywords: Bioclimatic analysis; Bioclimatic chart; Passive strategies; Solar radiation